Superparaelectric (Ba0.95, Sr0.05)(Zr0.2, Ti0.8)O3 Ultracapacitors. Issue 37 (31st August 2020) - Wang, Kun; Ouyang, Jun; Wuttig, Manfred; Zhao, Yu‐Yao; Cheng, Hongbo; Zhang, Yuan; Su, Rongxuan; Yan, Jing; Zhong, Xiangli; Zeng, Fei
Abstract: Analogous to the superparamagnetic state, a superparaelectric state is both scientifically intriguing and technologically important. In this state, a ferroelectric material shows a high dielectric constant and a nonhysteretic response to an external electric field, ideal for high k and capacitive energy storage applications. Despite many explorative studies, only circumstantial evidences for its existence are reported. Here, the existence of a superparaelectric state is directly proven in engineered nanocrystalline perovskite films of (Ba0.95, Sr0.05 )(Zr0.2, Ti0.8 )O3, which are grown on Si at a low temperature and consist of many well‐dispersed, nanometer‐size polar clusters. These nanoparticles are locally polar, and only lose their short‐range order after being heated up to ≈460 °C, above which they become paraelectrics. Furthermore, they collectively present a pseudo‐linear, frequency‐insensitive dielectric response, which is characterized by a close‐to‐zero remnant polarization and a large relative dielectric constant (≈65–70). Capacitors based on these superparaelectric films display high recyclable energy densities (≈100 J cm −3 ) and efficiencies (≈90%) at room temperature, as well as a reliable high field endurance and good frequency (up to ≈15 GHz) and temperature (up to ≈300 °C) stabilities in their dielectric properties. Abstract : This work directly proves that a superparaelectric state exists in nanocrystalline films of a conventional ferroelectric (Ba0.95, Sr0.05 )(Zr0.2, Ti0.8 )O3, which consist of many well‐dispersed nanometer polar clusters with an average diameter of 2–3 nm. These superparaelectric film capacitors display high recyclable energy densities (≈100 J cm −3 ) and efficiencies (≈90%), a reliable high‐field endurance, as well as good frequency and temperature stabilities.